Globalised Singapore brand : a study on Singapore Changi Airport's competitiveness. - Chu, Marvin Puay Kiat. (2010)
In the dynamic aviation industry, airports are continually implementing new strategies to strengthen their position as an air hub. With major trends such as deregulation and the rise of Low-Cost Carriers (LCCs) changing the aviation industry landscape, it is imperative for airports to adapt quickly to these ever-changing demands. This paper focuses on Singapore Changi Airport, a globally recognised air hub player. It studies the airport‘s successful business model and the factors contributing to its excellent reputation today. An analysis of the competitiveness of Changi Airport will be done in relation to its regional competitors in the East-Asian region. The ever-increasing competition in the aviation industry calls for the need to discuss the relevance of Changi Airport‘s strategies in the future. In essence, this paper will discuss in detail the position of Changi Airport in the airport industry and its vehement pursue towards the future as a successful Globalised Singapore Brand.